MYCORRHIZAE IN AGROFORESTRY: A CASE-STUDY - S.T. NUHAMARA (BIOTROPIA, 1987)
Census of mycorrhizae in Shorea javanica agroforests has been made periodically in the district of Krui, Lampung, Sumatra. Amanita hemibapha (Amanitaceae), Cantharellus cibarius (Cantharella-ceae), Lactarius spp., Russula spp. (Russulaceae) and Scleroderma sp. (Sclerodermataceae) were commonly encountered on the agroforest floor. These mycorrhizal fungi are naturally associated withÂ  the planted trees. The significance of mycorrhizae for the maximization of growth and sustained productivity of resin is discussed as well as the need to design well defined agroforestry systems to facilitate growth and to improve production management techniques.